Primary sedimentary structures in the porcellanites of Panda Valley, Bhaunathpur, Lower Vindhyan Basin, district Garhwa (old Palamu), Jharkhand (Journal of Nepal Geological Society, 2002)
Panda Valley consists of a thick pile of sediments in which there are three distinct Porcellanite horizons, Lower Porcellanite (LP), Middle Porcellanite (MP) and Upper Porcellanite (UP), with abundant sedimentary structures. The principle types of sedimentary structures noted in the Porcellanite Formation are discussed and an attempt has been made to interpret its depositional environment. The sedimentary structures are suggestive of deposition of sediments in low to moderately high energy, shallow to moderately deep waters in moderately stable tectonic environment.